Sudden cardiac death: clinical updates and perspectives : editorial - Schupp, Tobias; Akın, Ibrahim; Behnes, Michael (Journal of Clinical Medicine, 2022)
Sudden cardiac death (SCD) is defined as unexpected sudden death due to cardiac causes, occurring within one hour after the onset of symptoms [...]